Detection and isolation of Mycoplasma genitallium in evaporated urine from pregnant women by PCR method - Monireh Rahimkhani; Alireza Mordadi (Mashhad University of Medical Sciences, 2022)
Introduction: Mycoplasma is one of the most important bacterial causes of genital infections in women and men, followed by premature birth and even abortion in pregnant women. The present study was performed aimed to detect and isolate Mycoplasma genitallium in some pregnant women in first trimester of pregnancy. Methods: In this cross-sectional (descriptive-analytical) study which was performed in 2020-2021, evaporated urine sampling was collected from 66 pregnant women who were referred to the health center for screening tests on first trimester of pregnancy (between 11-14 weeks). In this way, these women did not urinate for at least 2 hours and then urine samples were collected in sterile containers. Urine sediment DNA was extracted and the genome of Mycoplasma was detected by PCR method. Data were analyzed by SPSS software (version 20) and Independent T-test. P<0.05 was considered statistically significant. Results: Mycoplasma genitallium genome was isolated from 17.65 % of evaporated urine sediment samples by PCR method. Conclusion: For isolation and detection of Mycoplasma in pregnant women, sampling of vaginal or cervix discharge have some dangers, thus evaporated urine sampling is a safer and more reliable method.